Los conflictos sobre el trasvase del Ebro y del Tajo - Villarroya Gil, Fermín (M+A. Revista Electrónica de Medioambiente, 2006)
From the environmental, economic and scientific point of view, the Ebro water diversion towards the East and South-eastern area of Spain is difficult to be accepted. Nevertheless, for a century, all the former governments have been promising to take water to those zones. This, together with to the good climatic conditions and the land disposition, has supposed an unstoppable process of spreading of the irrigable lands, and, therefore, an increase of the demand of water, totally untenable. The social conditions and sensitivity towards environment are not in these days same that do two or three decades before and of course those that existed in Spain when they fomented and they promised the big diversion of water. The problem is not of easy solution because from year 2000 a brand new Water Frame Directive exists in the countries of the UE who does not favours the policy of water transferences and, in case they take place, the costs must be supported completely by the users. The water use by the farmers probably will be nonviable. In addition, the environmental impact that would take place would be very remarkable. Nevertheless it will be necessary, as far as possible, to take care of the demands generated in all the Mediterranean area. The desalination, even though is very unaccepted by some ecologists, seems to be an acceptable partial solution. Before the¡ water transferences can take place seems to be necessary that a number of Groundwater User Communities must be launched such the Spanish Water Act envisaged. After twenty years of application of the Water Act none has been constituted. On the other hand, a good number of the boreholes and wells are illegal or are actually outside of the management of the Water Authority. The problem is very far from being solved. Meanwhile the politicians would have to be prone to assessment of the scientists and technicians and inform with veracity to the population the nature and reaches of the problem.
Keywords: Water diversion; Hydrological Plan; Water policy